Unique Biochemical and Mineral Composition of Whale Ear Bones - Kim, S.; Thewissen, J.; Churchill, M.; Suydam, R.; Ketten, Darlene; Clementz, M. (The University of Chicago Press, 2014)
Cetaceans are obligate aquatic mammals derived from terrestrial artiodactyls. The defining characteristic of cetaceans is a thick and dense lip (pachyosteosclerotic involucrum) of an ear bone (the tympanic). This unique feature is absent in modern terrestrial artiodactyls and is suggested to be important in underwater hearing. Here, we investigate the mineralogical and biochemical properties of the involucrum, as these may hold clues to the aquatic adaptations of cetaceans. We compared bioapatites (enamel, dentine, cementum, and skeletal bone) of cetaceans with those of terrestrial artiodactyls and pachyosteosclerotic ribs of manatees (Sirenia). We investigated organic, carbonate, and mineral composition as well as crystal size and crystallinity index. In all studied variables, bioapatites of the cetacean involucrum were intermediate in composition and structure between those of tooth enamel on the one hand and those of dentine, cementum, and skeletal bone on the other. We also studied the amino acid composition of the cetacean involucrum relative to that of other skeletal bone. The central involucrum had low glycine and hydroxyproline concentrations but high concentrations of nonessential amino acids, unlike most bone samples but similar to the tympanic of hippos and the (pachyosteosclerotic) ribs of manatees. These amino acid results are evidence of rapid bone development. We hypothesize that the mineralogical and amino acid composition of cetacean bullae differs from that of other bone because of (1) functional modifications for underwater sound reception and (2) structural adaptations related to rapid ossification.